Transformative Climates and Accountable Governance - Edmondson, Beth; Levy, Stuart (Palgrave Studies in Environmental Transformation, Transition and Accountability, 2019)
'Transformative and Accountable Climate Governance describes the paradigmatic influences and frameworks within which transformations and transitions in light of a warming earth will occur. The book thereby pursues a multi-disciplinary angle and offers an impressive interdisciplinary approach with truly international outlook. In its entirety, the book is therefore of direct relevance for academia, practitioners and public policy specialists around the globe.' - Julia M. Puaschunder, Prize Fellow at the Inter-University Consortium of New York, USA This book explores the real-world consequences changing ideas and strategies have on effective climate governance. Its main focus is on why accountability matters - both for transformations and transitions in international climate change governance and how international support for environmentally responsible actions, and extending shared accountabilities, might strengthen climate governance globally. A main point of discussion is if and how better understanding of accountabilities and transformations in ecosystems dynamics, the capacities of organisms to adapt, migrate or otherwise respond to environmental or climatic changes, can improve climate governance mechanisms. Bringing together a diverse set of considerations from various fields of study, chapters examine responses to environmental transformations that occur during periods of climatic crisis, such as species depletion, industrialisation, de-industrialisation or urbanisation. Throughout, this book aims to further readers understanding of if or how accountable climate governance can reduce the risks of global political disorder and widespread conflict in the 21st century, arising from environmental transformations of depleted forests, re-routed waterways, coastlines impacted by sea level rises, changed rainfall patterns and industrial practices. Beth Edmondson is a senior lecturer in the School of Arts at Federation University Australia. Her research focuses on international responses to global climate change, the possibilities for order in the international political system, the nature of sovereignty and the scope of international law in constructing governmental capacities. Stuart Levy is a senior lecturer in the School of Education at Federation University Australia. His interests in international relations include the nature and evolution of state sovereignty and the politics of global climate change. .